Pesticide use and incident diabetes among wives of farmers in the Agricultural Health Study. Issue 9 (12th April 2014) - Starling, Anne P; Umbach, David M; Kamel, Freya; Long, Stuart; Sandler, Dale P; Hoppin, Jane A
Abstract : Objective: To estimate associations between use of specific agricultural pesticides and incident diabetes in women. Methods: We used data from the Agricultural Health Study, a large prospective cohort of pesticide applicators and their spouses in Iowa and North Carolina. For comparability with previous studies of farmers, we limited analysis to 13 637 farmers' wives who reported ever personally mixing or applying pesticides at enrolment (1993–1997), who provided complete data on required covariates and diabetes diagnosis and who reported no previous diagnosis of diabetes at enrolment. Participants reported ever-use of 50 specific pesticides at enrolment and incident diabetes at one of two follow-up interviews within an average of 12 years of enrolment. We fit Cox proportional hazards models with age as the time scale and adjusting for state and body mass index to estimate HRs and 95% CIs for each of the 45 pesticides with sufficient users. Results: Five pesticides were positively associated with incident diabetes (n=688; 5%): three organophosphates, fonofos (HR=1.56, 95% CI 1.11 to 2.19), phorate (HR=1.57, 95% CI 1.14 to 2.16) and parathion (HR=1.61, 95% CI 1.05 to 2.46); the organochlorine dieldrin (HR=1.99, 95% CI 1.12 to 3.54); and the herbicide 2, 4, 5-T/2, 4, 5-TP (HR=1.59, 95% CI 1.00 to 2.51). With phorate and fonofos together in one model to account for their correlation, risks for both remained elevated, though attenuated compared with separate models. Conclusions: Results are consistent with previous studies reporting an association between specific organochlorines and diabetes and add to growing evidence that certain organophosphates also may increase risk.